Nrf2-Mediated Ferroptosis Inhibition Exerts a Protective Effect on Acute-on-Chronic Liver Failure. (16th April 2022) - Wu, Jing; Xue, Ran; Wu, Muchen; Yin, Xuehong; Xie, Bangxiang; Meng, Qinghua
Abstract : Although massive hepatocyte cell death and oxidative stress constitute major events of acute-on-chronic liver failure (ACLF), the relationship of ferroptosis with ACLF has yet to be explored. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key regulator of ferroptosis. However, if Nrf2 modulates ACLF through ferroptosis remains unknown. Here, the liver tissues of ACLF patients were collected and murine models of ACLF using carbon tetrachloride, D-galactosamine, and lipopolysaccharide as well as an H2 O2 -induced hepatocyte injury model were established. Upon ACLF, livers exhibited key features of ferroptosis, including lipid peroxidation (increase in malondialdehyde whereas a decrease in glutathione and nicotinamide adenine dinucleotide phosphate), and increased mRNA expression of prostaglandin-endoperoxide synthase-2 (PTGS2). Ferroptosis inducer RSL-3 treatment aggravated liver damage, while ferroptosis inhibitor Ferrostatin-1 administration alleviated ACLF severity, manifesting with improved liver histopathological lesions and reduced serum ALT and AST. Compared with normal liver tissue, Nrf2 was upregulated in ACLF patients and murine models. Pharmacological activation of Nrf2 (Bardoxolone Methyl) attenuated liver damage, prevented lipid peroxidation, upregulated PTGS2 mRNA expression, and improved ferroptosis-specific mitochondrial morphology in vivo. In contrast, Nrf2 inhibitor ML385 exacerbated lipid peroxidation and liver injury. Collectively, Nrf2 plays a protective role in ACLF progression through repressing ferroptosis, which provides promising therapeutic cues for ACLF.